Development of Web-based Spatial Information System Tourism Industry Event Distribution (Case Study: DKI Jakarta) - Muhammad Syaifullah Mahfudz; Zainul Arham; Eva Khudzaeva (Applied Information System and Management (AISM), 2020)
In recent years, the number and scope of events in the Asia and Middle East / North Africa region has increased significantly. Events are one of the things that attracts the attention of foreign tourists to come to visit a country as a tourist destination. Refers toMinister of Tourism Regulation Number 2 Year 2017on Guidelines for Venues for Meetings, Incentive Trips, Conventions and Exhibitions, explains that criteria and indicators are needed to increase the competitiveness of venues for meetings, incentive trips, conventions and exhibitions at the regional and global levels. This is done to increase the number of visits, length of stay, and expenditures for domestic and foreign tourists. Therefore, visual indicators or data are needed that can present the location of the event and a list of events in DKI Jakarta. From these problems, this study aims to produce a web-based spatial information system for the distribution of tourism industry events to map event locations in DKI Jakarta. The methodology used in collecting this data is the method of observation, interviews, and literature studies. While the system development methodology uses PHP and MySQL with the Rapid Application Development (RAD) approach and uses the Unified Modeling Language (UML) which is a tool for system description and design, as well as the Google Maps API for digital maps. The results of this study are in the form of a spatial information system that can display a map of the distribution of event locations in DKI Jakarta based on event data and event categories at the DKI Jakarta Tourism and Creative Economy Department. While the system development methodology uses PHP and MySQL with the Rapid Application Development (RAD) approach and uses the Unified Modeling Language (UML) which is a tool for describing and designing systems, as well as the Google Maps API for digital maps. The results of this study are in the form of a spatial information system that can display a map of the distribution of event locations in DKI Jakarta based on event data and event categories at the DKI Jakarta Tourism and Creative Economy Department. While the system development methodology uses PHP and MySQL with the Rapid Application Development (RAD) approach and uses the Unified Modeling Language (UML) which is a tool for describing and designing systems, as well as the Google Maps API for digital maps. The results of this study are in the form of a spatial information system that can display a map of the distribution of event locations in DKI Jakarta based on event data and event categories in the DKI Jakarta Tourism and Creative Economy Department.